This side of paradise ebook - Fitzgerald, F. Scott (Duke Classics, 2012)
This Side of Paradise is a novel about post-World War I youth and their morality. Amory Blaine is a young Princeton University student with an attractive face and an interest in literature. His greed and desire for social status warp the theme of love weaving through the story.